2015
DOI: 10.1007/s12032-015-0598-7
|View full text |Cite
|
Sign up to set email alerts
|

LRG1 suppresses the migration and invasion of hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) is a malignant tumor driven by complex pathological mechanisms and is characterized by fast progression and poor prognosis. The main cause of death in HCC patients is tumor metastasis. However, underlying molecular mechanisms of metastasis are largely unknown in HCC. In the present study, a novel metastasis-related gene, leucine-rich-alpha-2-glycoprotein 1 (LRG1), was identified in HCC. We revealed that LRG1 expression was downregulated in HCC tissues by quantitative real-time PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 21 publications
(27 reference statements)
5
22
0
Order By: Relevance
“…The high expression of LRG1 was found to promote the invasion and migration of those cancer cells. However, it has also been reported that the expression of LRG1 in liver cancer cell lines is lower than that in normal liver cells, and the overexpression of LRG1 could suppress the invasion and migration of liver cancer cells [18]. In our study, we first demonstrated that the levels of LRG1 mRNA were significantly decreased in patients with ESCC by mining of the GEO database, which appeared to be well maintained in several patient-derived cell lines.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The high expression of LRG1 was found to promote the invasion and migration of those cancer cells. However, it has also been reported that the expression of LRG1 in liver cancer cell lines is lower than that in normal liver cells, and the overexpression of LRG1 could suppress the invasion and migration of liver cancer cells [18]. In our study, we first demonstrated that the levels of LRG1 mRNA were significantly decreased in patients with ESCC by mining of the GEO database, which appeared to be well maintained in several patient-derived cell lines.…”
Section: Discussionsupporting
confidence: 55%
“…The expression levels of LRG1 were found to be upregulated in several types of carcinomas such as ovarian cancer and colorectal cancer, where it promotes tumor cell proliferation and invasion while inhibiting apoptosis [14][15][16][17]29]. However, there are also studies showing that LRG1 expression is down-regulated in tumors, inhibiting tumor cell proliferation while promoting apoptosis [18,19]. The impact of LRG1 on cell migration and invasion appeared to be controversial even in the same tumor type, such as hepatocellular carcinoma (HCC).…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…LRG1 expression has diverse cellular locations, including the nucleus, cytoplasm, plasma membrane, extracellular matrix, serum and cerebrospinal fluid (12,14,20). Nakajima et al (35) reported that LRG1 is distributed throughout the entire brain.…”
Section: Discussionmentioning
confidence: 99%
“…LRG1 is a highly conserved member of leucine-rich repeat (LRR) family of proteins, several of which are involved in protein-protein interactions, signaling transduction, cell adhesion, cell survival, cell apoptosis, cell metastasis, DNA transcription, DNA repair and RNA processing (1013). Zhang et al (14) reported that LRG1 was involved in the inhibition of hepatocellular carcinoma (HCC) metastasis and may function as a novel metastasis suppressor in HCC. Additionally, the function of LRG1 in tumors was investigated, and indicated that LRG1 was associated with multiple types of tumor, including ovarian cancer, glioblastoma and squamous cell lung cancer (1518).…”
Section: Introductionmentioning
confidence: 99%